Kinetic Investigation of Grafting of Methylmethacrylate-Acrylic Acid Mixture onto Poly(ethylene terephthalate) Fibers with Benzoyl Peroxide - Azizinezhad, Fariborz; Harutyunyan, Romic; Abdouss, Majid (Asian Journal of Chemistry, 2010)
In this study the rate of grafting and some kinetic parameters of the graft copolymerization of (methylmethacrylate-acrylic acid) mixture onto poly(ethylene terephthalate) fibers with benzoyl peroxide was investigated. The rate of grafting was found to the 1.63 and 0.88 powers of monomer mixture and initiator concentrations, respectively. The activation energy (64.15 kJ/mol) of the reaction at four different temperature from 343 to 358 K, was calculated. As mentioned below, the use of anionic and cationic emulsifiers cause a decrease in graft product and on the other hand with the use of initiators mixture such as benzoyl peroxide and potassium persulphate (Bz2O2-KPS) the graft product has a decreased. However with the increase of graft, intrinsic viscosity increased and density decreased.